CORRELATION BETWEEN LIVER TRANSAMINASE ENZYME AND LEUKOCYTE COUNT IN TUBERCULOSIS PATIENTS WHO RECEIVED ANTI-TUBERCULOSIS DRUG THERAPY - Kayla Navazia Marlie; Edward Kurnia Setiawan Limijadi; Meita Hendrianingtyas; Dwi Retnoningrum (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: While effective in treating the disease, anti-tuberculosis drugs can also potentially harm the liver. Monitoring liver health using the transaminase enzyme and leukocyte counts can help in the early detection and prevention of such damage in tuberculosis patients. Objectives: The aim of the study was to determine the correlation between transaminase enzyme levels and the leukocyte count in patients with tuberculosis who took anti-tuberculosis drugs. Methods: This research was an observational analytical study with a cross-sectional approach. It used medical record data from TB patients who met the inclusion and exclusion criteria for anti-tuberculosis drug therapy at the medical records installation. Results: Forty-four samples were included in the research. The levels of aspartate transaminase (AST), alanine transaminase (ALT), and leukocyte count were 30 IU/L, 19.5 IU/L, and 9.35x103/µL. The Spearman correlation test showed no correlation between AST and ALT levels and leukocyte counts, with p-values of 0.585 and 0.337. Conclusion: There was no correlation between AST and ALT levels and leukocyte counts in tuberculosis patients undergoing anti-tuberculosis drug therapy.